2022
DOI: 10.1088/1757-899x/1258/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electrical properties of bismuth sodium titanate ceramic

Abstract: Single-phase lead-free Bi0.5Na0.5TiO3 (BNT) perovskite ferroelectric ceramic was produced using a solid-state reaction method. A detailed investigation of the structural and electrical properties of BNT ceramic is conferred. According to phase analysis employing Rietveld refined X-Ray diffraction, the crystal structure is single phase with rhombohedral (R3C) symmetry. Raman spectra measurement also confirms the rhombohedral structure of BNT by originating numerous peaks from the TiO6 octahedron. The ferroelect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Peaks at 1412.4 1 and 1415.3 cm –1 in NBT/rGO and NBT/WrGO nanocomposites, respectively, arise to the C–OH stretching vibrations of rGO. The Bi–O stretching vibration at 643.1 cm –1 in the case the of bare NBT shifts to 632.7 and 641.3 cm –1 for the NBT/rGO and NBT/WrGO nanocomposites, respectively, owing to the strong interaction of NBT with rGO. , The Ti–O stretching band for NBT centered at 454.4 cm –1 significantly shifts to 428.8 and 440.2 cm –1 in the case of NBT/rGO and NBT/WrGO nanocomposites on account of the strong interaction of NBT with rGO …”
Section: Resultsmentioning
confidence: 95%
“…Peaks at 1412.4 1 and 1415.3 cm –1 in NBT/rGO and NBT/WrGO nanocomposites, respectively, arise to the C–OH stretching vibrations of rGO. The Bi–O stretching vibration at 643.1 cm –1 in the case the of bare NBT shifts to 632.7 and 641.3 cm –1 for the NBT/rGO and NBT/WrGO nanocomposites, respectively, owing to the strong interaction of NBT with rGO. , The Ti–O stretching band for NBT centered at 454.4 cm –1 significantly shifts to 428.8 and 440.2 cm –1 in the case of NBT/rGO and NBT/WrGO nanocomposites on account of the strong interaction of NBT with rGO …”
Section: Resultsmentioning
confidence: 95%
“…In continuation to our earlier review on perovskite materials (1) and extraction of thorium (2), we have reported here the various synthesis routes of graphene and graphene oxide with their characteristics and applications. Graphene is a hexagonal planner carbon ring which is derived from 3D massive covalent structured graphite.…”
Section: Introductionmentioning
confidence: 89%